Impact of Macroeconomic Factors on Underpricing: Case of Indonesia Stock Exchange - Aulia Amin Nasution; Ali Mutasowifin (InFestasi, 2021)
The stock market is one of the alternatives chosen by companies to meet their funding needs. The first offering of a company's shares through the stock market to investors is called an Initial Public Offering. At the time of initial public offering, underpricing often occurs when the initial stock price on the primary market is lower than the stock price on the secondary market which will disadvantage the company because the collected funds are not maximum. This research aims to analyze the effect of macroeconomic factors on underpricing in companies conducting IPOs listed on the Indonesia Stock Exchange from 2010 to 2020. Using Regression Linear Analyze we found that macroeconomic variables as Inflation, IDX Composite Index, and GDP significantly affect underpricing on IPO in Indonesia Stock Exchange for 2010 to 2020